Child Marriage from the Perspective of Hadith in the Hermeneutic Study of Muhammad Syahrur - Mawardi; Umi Sumbulah; Fakhruddin (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2025)
Early marriage has become a controversial topic in religious and social studies, particularly from the perspective of Islamic law. Hadith provides guidance on marriage, which is often interpreted in diverse ways. This article examines early marriage from the perspective of hadith using Muhammad Shahrur's hermeneutics to understand the relevance of traditional views in a modern context. The study aims to explore Shahrur's interpretative method, which emphasizes contextualizing meaning, and to identify potential implications for Islamic marriage law. The method used is a qualitative approach with content analysis of hadith texts, supported by relevant literature. The findings indicate that Shahrur's hermeneutical method offers a new perspective on understanding hadith related to early marriage, which can strengthen arguments for adjusting the marriage age to align with socio-cultural conditions.